(untitled) (Measurement Science Review, 2026)
Operational amplifiers are an important ingredient of analogue electronic circuits, and their noise performance is an essential design parameter. However, at low frequencies, data provided by component manufacturers usually cover only a limited range (typically 0.1 Hz to 10 Hz). The frequencies below this range, critical for high-stability and precision circuits, such as signal conditioning stages, voltage references, or digitizing voltmeters, are rarely addressed. Therefore, it is often necessary to characterize the parts. The traditional noise measurement technique requires the amplifier to be configured for very high gain, which is seldom the way the amplifier is used. Different techniques for voltage noise density measurement are presented and compared in this paper, including two methods that allow for noise measurement with a unity gain configuration - a mode that has not been explored until now. Practical aspects required to obtain reliable results are highlighted. A side product of this work is an open-hardware design of an ultra low-noise amplifier, which can be used to measure the noise performance of operational amplifiers or resistors using regular measuring equipment readily available at universities or industrial laboratories.